Representations of cultural encounters in the global business press – The importance of cross-cultural competence - Haarala, Karl (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2015)
This qualitative study has started from the interest to examine how the reality of crosscultural encounters is presented in the global business press. The research paper emphasizes different ways to classify culture and cross-cultural competency, both from the point of view of individuals and organizations. The analysis consists of public discourses, where cross-cultural realities are created through different persons, stories and contexts For data collection, a comprehensive database search was performed and 10 articles from the widely known worldwide business magazine The Financial Times were chosen as the data for the study paper. For the functions of addressing the research study questions, Thematic Content Analysis (TCA) and also Discourse Analysis (DA) are utilized, added with the continuous comparison method of grounded theory in the formation of the data.The academic references consist of literary works and articles presenting relevant concepts, creating a cross-cultural framework, and it is designed to assist the reader in the navigation through the topics of culture and cross-cultural competency. The repertoires were formed from the data and following, the first repertoire is contrast difference between home and target culture that the individual was able to discern. As a consequence of the first repertoire, the companies then offer cultural training to their employees to prepare them to situations of increasing levels of cultural variation. The third repertoire is increased awareness of other cultures, which is conveyed as a result of cultural training and contextual work experience. The fourth repertoire is globalization as an international business environment, where the people in the articles perform their job functions. It is stated in the conclusions that the representations emphasize Western values and personal traits in leadership.